(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the severity of hypothermia and some related factors in vascular surgery patients at Bach Mai Hospital. Research methods: A cross-sectional descriptive study design was conducted on 101 patients undergoing major vascular surgery at the Anesthesia and Resuscitation Center and the Thoracic Surgery Department, Bach Mai Hospital, from December 2024 to November 2025. Results: The study patients had an average age of 68.12 ± 10.58; the proportion of males was 86.1%; the majority were ASA II-III and had comorbidities. The rate of intraoperative hypothermia was 67.3%, of which 98.5% were mild, 1.5% severe, and no moderate cases were recorded. The average surgical time was 152.48 ± 46.08 minutes. Hypothermia showed statistically significant differences with factors such as pulse rate, prolonged surgical time, and amount of blood products transfused (p < 0.05), but no statistically significant differences with factors such as gender, BMI, ASA, underlying disease, anesthesia method, or warming measures applied. Conclusion: Intraoperative hypothermia in vascular surgery patients at Bach Mai Hospital remains common, mostly mild. Prolonged surgical time and blood product transfusions are related factors. It is recommended to strengthen proactive hypothermia prevention measures in high-risk groups.